A Mobile Technology for Collecting Patient-Reported Physical Activity and Distress Outcomes: Cross-Sectional Cohort Study - Jung, Miyeon; Lee, SaeByul; Kim, Jisun; Kim, HeeJeong; Ko, BeomSeok; Son, Byung Ho; Ahn, Sei-Hyun; Park, Yu Rang; Cho, Daegon; Chung, Haekwon; Park, Hye Jin; Lee, Minsun; et al. (JMIR Publications, 2020)
BackgroundElectronic patient-reported outcome (PROs) provides a fast and reliable assessment of a patient's health-related quality of life. Nevertheless, using PRO in the traditional paper format is not practical for clinical practice due to the limitations associated with data analysis and management. A questionnaire app was developed to address the need for a practical way to group and use distress and physical activity assessment tools. ObjectiveThe purpose of this study was to assess the level of agreement between electronic (mobile) and paper-and-pencil questionnaire responses. MethodsWe validated the app version of the distress thermometer (DT), International Physical Activity Questionnaire (IPAQ), and Patient Health Questionnaire-9 (PHQ-9). A total of 102 participants answered the paper and app versions of the DT and IPAQ, and 96 people completed the PHQ-9. The study outcomes were the correlation of the data between the paper-and-pencil and app versions. ResultsA total of 106 consecutive breast cancer patients were enrolled and analyzed for validation of paper and electronic (app) versions. The Spearman correlation values of paper and app surveys for patients who responded to the DT questionnaire within 7 days, within 3 days, and on the same day were .415 (P<.001), .437 (P<.001), and .603 (P<.001), respectively. Similarly, the paper and app survey correlation values of the IPAQ total physical activity metabolic equivalent of task (MET; Q2-6) were .291 (P=.003), .324 (P=.005), and .427 (P=.01), respectively. The correlation of the sum of the Patient Health Questionnaire-9 (Q1-9) according to the time interval between the paper-based questionnaire and the app-based questionnaire was .469 for 14 days (P<.001), .574 for 7 days (P<.001), .593 for 3 days (P<.001), and .512 for the same day (P=.03). These were all statistically significant. Similarly, the correlation of the PHQ (Q10) value according to the time interval between the paper-based questionnaire and the app-based questionnaire was .283 for 14 days (P=.005), .409 for 7 days (P=.001), .415 for 3 days (P=.009), and .736 for the same day (P=.001). These were all statistically significant. In the overall trend, the shorter the interval between the paper-and-pencil questionnaire and the app-based questionnaire, the higher the correlation value. ConclusionsThe app version of the distress and physical activity questionnaires has shown validity and a high level of association with the paper-based DT, IPAQ (Q2-6), and PHQ-9. The app-based questionnaires were not inferior to their respective paper versions and confirm the feasibility for their use in clinical practice. The high correlation between paper and mobile app data allows the use of new mobile apps to benefit the overall health care system. Trial RegistrationClinicalTrials.gov NCT03072966; https://clinicaltrials.gov/ct2/show/NCT03072966